Properties and characteristics of thermoplastic PBT-LCP blend system and the influence of nanosilica-380 - Ng, Vincent Zhijie. (2012)
Blends of polybutylene terephthalate (PBT) and glass fibre reinforced liquid crystalline polymer (LCP A130) have been prepared by the melt mixing technique by the twin screw extruder device. The study was to evaluate the various properties of thermoplastic polymer systems with and without nanosilica-380 fillers. Specimens were moulded into different shapes with dimensions suitable for different characterizations. The SEM results indicate the increase in LCP content increase the fibers of the blend system and addition of hydrophilic nano-silica improved dispersion. The XRD study showed that the incorporation of LCP in larger quantities hindered the development of certain morphology of the PBT-LCP blend system. The FTIR spectra showed shift in peaks under the influence of nano-silica which indicates signs of better dispersion. The DMA study shows that the addition of nano-silica filler improves the storage modulus and lowers the loss factor for the polymer blend. The TGA results show that the increase in LCP content and the incorporation of nano-silica improved thermal stability of the polymer blend system. Finally, the tensile test results indicate enhancement in mechanical properties by adding nano-silica filler or more LCP into the system.